The Application of the Listening in Action Method Assisted by Doratoon Animated Video Media in Learning to Identify Hikayat Texts - Balqis Sahla Aqila; Titin Nurhayatin; Rendy Triandy (Global Action and Education for Society, 2025)
The low ability of students to understand hikayat text material is the background for this research. The use of less innovative and creative methods and media makes learning seem boring and students less interested in participating. Therefore, the author wishes to conduct research using the Listening in Action method assisted by Doratoon animated video media. With the aim of testing whether there is a significant difference in the ability to identify hikayat texts between experimental class students and control class students. The method used by the author in this study is the experimental quantitative method, using a Quasi Experimental Design. This is proven by looking at the results of the Independent Samples t-test. The sig. result of this test is 0.013 < 0.050, which means there is a significant result. This difference can be proven by the average scores obtained by the students. The average pretest score for the experimental class increased from 51.03 to 81.68 in the posttest results. The average for the control class increased from 47.65 to 74.71 in the posttest results. There was a significant difference between the learning outcomes of students in the experimental and control classes, with the posttest average score in the experimental class being 81.68, while in the control class it was 74.71. Thus, the learning that was done can be said to have been successful.